Bez hormonow i bez strachu : naturalne przejscie przez menopauze - Posner, Trisha; Czernicka, Malgorzata (Wroclaw : Wydawnictwo Dolnoslaskie, 2003)
Polish translation of "No hormones, no fear". A popular work for women about the means of overcoming menopause afflictions without medications.
Translation of: No hormones, no fear.
Keywords: Menopause -- Popular works